Old Concepts, New Application – Additive‐Free Hydrogenation of Nitriles Catalyzed by an Air Stable Alkyl Mn(I) Complex - Weber, Stefan (Adv Synth Catal, 2019)
An efficient additive‐free manganese‐catalyzed hydrogenation of nitriles to primary amines with molecular hydrogen is described. The pre‐catalyst, a well‐defined bench‐stable alkyl bisphosphine Mn(I) complex fac‐[Mn(dpre)(CO)(3)(CH(3))] (dpre=1,2‐bis(di‐n‐propylphosphino)ethane), undergoes CO migratory insertion into the manganese‐alkyl bond to form acyl complexes which upon hydrogenolysis yields the active coordinatively unsaturated Mn(I) hydride catalyst [Mn(dpre)(CO)(2)(H)]. A range of aromatic and aliphatic nitriles were efficiently and selectively converted into primary amines in good to excellent yields. The hydrogenation of nitriles proceeds at 100 °C with a catalyst loading of 2 mol % and a hydrogen pressure of 50 bar. Mechanistic insights are provided by means of DFT calculations. [Image: see text]